Avaliação de coleções e de serviços de bibliotecas para a área de ciência da computação - Castilho, Rosane Teles Lins (1978)
The "document delivery test" developed by Orr has been found applicable to measure the capability of brazilian libraries to provide documents in the field of Computer Science. Two samples have been used to test the libraries’ capabilites : a sample of citations obtained randomly from articles published in the journal "Computing Surveys", and a citation pool obtained from the series of technical reports published by the Computer Science Department (Departamento de Informática) of the Pontifícia Universidade of Rio de Janeiro. It was concluded that the potential capability of the document delivery test to indicate the ability of the libraries to deliver documents not owned had been reduced because the interlibrary loan service records were inadequate to permit a realistic estimate of the wating time for borrowing such documents. The results obtained were influenced by factors related to the characteristics of the items of the tests, with the characteristics of the collections and with the infra-structure of the libraries services being tested, and suggest that these libraries show relatively low document delivery capability indices.